PERANAN KOMISI PENGAWAS PERSAINGAN USAHA TERHADAP INFLASI HARGA OBAT SELAMA PANDEMI COVID-19 - Tiya Nur’aini; Ariawan Gunandi (Jurnal Hukum Adigama, 2021)
During the Covid-19 Pandemic, many negative impacts on life in general, such as a problem that newis currently occurring, namely the increase or inflation of drug prices, many business actors make this event a large profit field and can add to problems such as hoarding is an example of the case, namely the hoarding of drugs by PT ASA which also increases the selling price of its drugs and raises prices beyond the MRT(maximum retail price) provisions which can lead to monopolistic practices and unfair business competition between business actors. with the main problem: What is the role of the Business Competition Supervisory Commission (BCSC) on Drug Price Inflation During the Covid-19 Pandemic? . The method use a normative research that the results of this study indicate that problems with inflation or drug prices increase must be addressed by the Business Competition Supervisory Commission (BCSC) in carrying out its role in efforts to prevent monopolistic practices and business competition in every business activity and can foster a conducive business climate through the creation of fair business competition, and prevent monopolistic practices and or unfair business competition caused by business actors, as well as create effectiveness and efficiency in business activities in the context of increasing national economic efficiency as one of the efforts to improve people's welfare is the objective of BCSC in Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition.